The Effect Of Cellulase Content On Phytoestrogens Formation (Genistein) Materials On Fermented Soybean Waste Aspergillus niger - Vara Tassa Sutari; Nurliana Nurliana; Sugito Sugito; Darmawi Darmawi; Rinidar Rinidar (The International Journal of Tropical Veterinary and Biomedical Research, 2018)
The activity of the cellulase enzyme and the content of phytoestrogen (genistein) forming is determined during the fermentation of soybean waste with Aspergullus niger. The analysis is performed at fermentation incubation time of 0, 48, 96, 144 and 192 hours and treatment with addition of micro nutrient (V2) and without micro nutrient (V1). Data analysis on cellulase enzyme activity on phytoestrogen forming material is performed using T test. The average of cellulase content of fermented soybean waste increases from 0.032-0.139 IU / ml (V1) and 0.061-0.158 IU / ml (V2) after 48 hours into 0.238 IU / ml (V1) and 0.245 IU / ml (V2) after 192 hours The average of genestein levels in the fermented soybean waste increases as well from 0.101 - 0.573 mg / g (V1) and 0.114 - 0.587 mg / g (V2) after 48 hours and increase into 0.722 mg / g (V1) and 0.699 mg / g (V2) after 192 hours. Statistical analysis indicates that the treatment of V1 and V2 has an effect on the increase of cellulase enzyme content and genistein level (P 0.05). The correlation between enzyme activity of cellulase and genistein on soybean waste fermented with Aspergillus niger is significant (R2 = 0,949). The relationship between the enzyme performance and its formation material is running synergistic, cellulase enzyme activity and genistein level experience significant increase during the fermentation process.